Phosphoinositide metabolism links cGMP-dependent protein kinase G to essential Ca²⁺ signals at key decision points in the life cycle of malaria parasites. - Mathieu Brochet; Mark O Collins; Terry K Smith; Eloise Thompson; Sarah Sebastian; Katrin Volkmann; Frank Schwach; Lia Chappell; Ana Rita Gomes; Matthew Berriman; Julian C Rayner; David A Baker; et al. (PLoS Biology)
Many critical events in the Plasmodium life cycle rely on the controlled release of Ca²⁺ from intracellular stores to activate stage-specific Ca²⁺-dependent protein kinases. Using the motility of Plasmodium berghei ookinetes as a signalling paradigm, we show that the cyclic guanosine monophosphate (cGMP)-dependent protein kinase, PKG, maintains the elevated level of cytosolic Ca²⁺ required for gliding motility. We find that the same PKG-dependent pathway operates upstream of the Ca²⁺ signals that mediate activation of P. berghei gametocytes in the mosquito and egress of Plasmodium falciparum merozoites from infected human erythrocytes. Perturbations of PKG signalling in gliding ookinetes have a marked impact on the phosphoproteome, with a significant enrichment of in vivo regulated sites in multiple pathways including vesicular trafficking and phosphoinositide metabolism. A global analysis of cellular phospholipids demonstrates that in gliding ookinetes PKG controls phosphoinositide biosynthesis, possibly through the subcellular localisation or activity of lipid kinases. Similarly, phosphoinositide metabolism links PKG to egress of P. falciparum merozoites, where inhibition of PKG blocks hydrolysis of phosphatidylinostitol (4,5)-bisphosphate. In the face of an increasing complexity of signalling through multiple Ca²⁺ effectors, PKG emerges as a unifying factor to control multiple cellular Ca²⁺ signals essential for malaria parasite development and transmission.